NFκB in Intrinsic and Cell Autonomous Regulation of Mesenchymal Stem Cell Multipotency - Sherman, Lauren S.; Jihayel, Jad A.; Correa-Velloso, Juliana; Lukac, Sophia P.; Liu, Cassie Y.; Greco, Steven J.; Harby, Clara B.; Ulrich, Henning; Rameshwar, Pranela (International Journal of Translational Science, 2026)
Mesenchymal stem cells (MSCs) are multipotent stromal cells that can differentiate into cells of the three germ layers. MSCs exhibit immune plasticity and this property is guided by the inflammatory tissue niche. Importantly, MSCs can be licensed as immune suppressor cells within an inflammatory niche. Since MSCs are approved by the food and drug administration for particular inflammation, it is important to determine how these cells maintain multipotency, in particular, the fate of these cells in vivo when they become located within a varied tissue niche. More importantly, the molecular mechanisms by which MSCs maintain multipotency will improve clinical applications. The focus of this study is particularly important since MSCs are available off the shelf, indicating allogeneic differences between the recipient and donor. We studied the transcription factor NFκB since it is a central regulator of inflammation. NFκB also links intrinsic stem cell signaling and extrinsic inflammatory cues. We used in silico analyses and determined that NFκB could regulate the major stem cell genes such as Octamer 4A (Oct4A). We confirmed a canonical pathway using an NFκB array that dissected the intracellular pathway. Additionally, we used specific small molecules to inhibit NFκB subunits. Using published RNA-Seq data, we showed a potential role for the purinergic receptors with a key role for ADORA2B. Similar to the licensing of MSCs by inflammatory mediators, ADORA2B appeared to be regulated by growth factors, including those linked to inflammation. In total, NFκB regulates MSC multipotency in a cell-autonomous manner, explaining the licensing properties within an inflammatory microenvironment. We also showed that the purinergic receptors could be involved in intrinsic and extrinsic regulation of MSC multipotency.